PENERAPAN SURAT KETETAPAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM UPAYA MENINGKATKAN PENERIMAAN PPH ORANG PRIBADI - Andi Rustam; Della Fadhilatunisa; Nurfasilah Nurfasilah (Universitas Muhammadiyah Makassar, 2020)
Taxpayer compliance is seen from the notification letter reported by the taxpayer. The tax assessment letter can be seen from the number of tax assessment letters issued. This study uses secondary data obtained from the West Makassar Primary Tax Office for 2016 to 2018 by using data collection documentation and data analysis techniques. The results of the study prove that taxpayer compliance and tax assessment letters affect the income tax on personal income in West Makassar Primary Tax Office. Based on the level of the ratio of tax revenue to income tax assessments each year from 0.5% to 23.8%. The benefit gained from this research is to provide answers to the problems studied and can be used as input for those who experience and are directly involved with this title.